Impulsive Buying in Gen Z: How Online Customer Review, Sales Promotion, and Conformity Influence Impulsive Buying through Consumer Trust (Study on E-Commerce Users in Purwokerto) - Putri, Tri Iriani; Astuti, Herni Justiana (MultiTech Publisher, 2024)
This research aims to examine the effect of online customer reviews, sales promotions, and suitability on impulse buying through customer trust as mediating variables. The sample taken in this study were 108 Gen Z e-commerce users in Purwokerto using a purposive sampling technique. The method of analysis used in this research is descriptive quantitative and uses smart PLS 3.0. Data collection techniques through questionnaires. The research results show that sales promotions and conformity can affect impulse buying. Online customer reviews do not affect impulse buying. Customer trust can mediate conformity to impulsive buying but cannot mediate online customer reviews and sales promotion.